2004
DOI: 10.1074/jbc.m307137200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Class of Endoperoxides from Arachidonate Autoxidation

Abstract: Free radical-initiated lipid autoxidation in low density lipoprotein (LDL) has been implicated in the pathogenesis of atherosclerosis. Oxidation of the lipid components of LDL leads to a complex mixture of hydroperoxides, bicyclic endoperoxides, monocyclic peroxides, and serial cyclic peroxides. The oxidation compounds and/or their decomposition products can modify protein components, which may lead to various diseases. A novel class of peroxides (termed dioxolane-isoprostanes) having a bicyclic endoperoxide m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 39 publications
1
56
0
2
Order By: Relevance
“…As is evident, the 7-and 17-series are major regioisomers compared with the 14-and 10-series. The formation of dioxolane-isoprostanes from 14-and 10-series isomers may be responsible for the regioselectivity, as in the case of arachidonate oxidation (29). In combination, these structural data from derivatization, CID, and SRM experiments establish that the F 2 -IsoP-like compounds generated from AdA oxidation are F 2 -dihomo-IsoPs.…”
Section: Identification and Quantification Of Unesterified Ada Productsmentioning
confidence: 76%
“…As is evident, the 7-and 17-series are major regioisomers compared with the 14-and 10-series. The formation of dioxolane-isoprostanes from 14-and 10-series isomers may be responsible for the regioselectivity, as in the case of arachidonate oxidation (29). In combination, these structural data from derivatization, CID, and SRM experiments establish that the F 2 -IsoP-like compounds generated from AdA oxidation are F 2 -dihomo-IsoPs.…”
Section: Identification and Quantification Of Unesterified Ada Productsmentioning
confidence: 76%
“…Such regioisomeric predominance has also been reported for F 2 -IsoP regioisomers in which 5-and 15-series compounds are formed in greater abundance than 8-and 12-series molecules (27). At least part of the reason for this is likely due to the fact that precursors of 8-and 12-series F 2 -IsoPs can undergo further oxidation and cyclization to yield a novel class of compounds termed dioxolane endoperoxides (41). Although undetermined at present, it is likely that a similar mechanism may account for the predominance of 5-and 18-series F 3 -IsoPs.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the predicted oxidation products of EPA have cyclic peroxide moieties and are unstable when analyzed by conventional ESI-MS. However, a milder ionization technique, Ag ϩ CIS-MS, has proven to be useful in identification of these intact peroxides based on characteristic fragmentation induced by Ag ϩ coordination of lipids (30,32,33). Furthermore, the doublet peaks in the Ag ϩ CIS spectra are characteristic of silver adducts because silver has two isotopes 107 daltons and 109 daltons with almost equal abundance.…”
Section: Identification Of Intact Peroxides From the Oxidation Of Epamentioning
confidence: 99%
“…As would be predicted based on our unified mechanism of EPA oxidation, six series of F 3 -IsoPs are formed from EPA whereas only four series of F 2 -IsoPs are generated from arachidonic acid. We have previously shown that 5-and 15-series F 2 -IsoPs are formed in greater abundance than 8-and 12-series F 2 -IsoPs because the precursors that lead to 8-and 12-series F 2 -IsoPs can further cyclized to form dioxolaneIsoPs (33). Similarly, we would predict that the oxidation of EPA will lead to the preferential generation of 5-and 18-series F 3 -IsoPs compared with 8-, 12-, 11-, and 15-series compounds because the precursors of the latter F 3 -IsoPs can undergo further oxidation to form dioxolane-IsoPs and bis-dioxolaneIsoPs.…”
Section: Identification Of Novel Oxidation Products From Epa In Vivo-mentioning
confidence: 99%